Survival of Lassa Virus in Blood and Tissue Culture Media and in a Small Particle Aerosol - Sophie J Smither; Lin S Eastaugh; James S Findlay; Lyn M O’Brien; Mark S Lever (Pathogens, 2020)
Knowledge of the survival and stability of a pathogen is important for understanding its risk, reducing its transmission, and establishing control measures. Lassa virus is endemic in West Africa, causes severe disease, and is an emerging pathogen of concern. Our study examined the survival of Lassa virus in blood and tissue culture media at two different temperatures. The stability of Lassa virus held within a small particle aerosol was also measured. In liquids, Lassa virus was found to decay more quickly at 30 °C compared to room temperature. Sealed samples protected from environmental desiccation were more stable than samples open to the environment. In a small particle aerosol, the decay rate of Lassa virus was determined at 2.69% per minute. This information can contribute to risk assessments and inform mitigation strategies in the event of an outbreak of Lassa virus.